US COUNTER-TERRORISM WAR 2003 AND THE OPERATIONS OF TERRORIST NETWORKS IN IRAQ - Odoemene, Robert Chinonyerem; Ofuebe, Chikelue (African Journal of Social and Behavioural Sciences, 2021)
This study is focused on US counter-terrorism war 2003 and its effects on the operations of terrorist networks in Iraq. It examined the invasion and forcible occupation of Iraq by the United States as a reaction to the September, 11 2001 attack on the United States. The objectives of the study included, to find out how the strategy adopted in the counter-terrorism war affected the operations of terrorist networks, especially al-Qaeda and ISIS, understanding what actually motivated the US invasion of Iraq when none of the 19 attackers of the 9/11 was an Iraqi citizen and to suggest how the negative effects of the war on terror can be ameliorated on the people of Iraq. The study adopted the securitization theory as a framework of analysis. Qualitative method of data collection and analysis was used to collect and analyze the secondary data. Part of the findings was that the US government technically securitized terrorism in order to use it as a cloak in furtherance of its imperialistic and commercial diplomacy in Iraq. Against this backdrop, the study came to the conclusion that though terrorism posed a global security challenge, the application of hard security (war) to stem terrorism was tantamount to using ‗terrorism‘ to fight terrorism. Therefore it was recommended among others that the United States should review its counter-terrorism policy and adopt non-military measures rather than armed confrontations to counter international terrorism